AAV vectors displaying bispecific DARPins enable dual-control targeted gene delivery - Theuerkauf, Samuel; Herrera-Carrillo, Elena; John, Fabian; Zinser, Luca J.; Molina, Mariano A.; Riechert, Vanessa; Thalheimer, Frederic B.; Börner, Kathleen; Grimm, Dirk; Chlanda, Petr; Berkhout, Ben; Buchholz, Christian J. (Biomaterials, 2023)
Precise delivery of genes to therapy-relevant cells is crucial for in vivo gene therapy. Receptor-targeting as prime strategy for this purpose is limited to cell types defined by a single cell-surface marker. Many target cells are characterized by combinations of more than one marker, such as the HIV reservoir cells. Here, we explored the tropism of adeno-associated viral vectors (AAV2) displaying designed ankyrin repeat proteins (DARPins) mono- and bispecific for CD4 and CD32a. Cryo-electron tomography revealed an unaltered capsid structure in the presence of DARPins. Surprisingly, bispecific AAVs transduced CD4/CD32a double-positive cells at much higher efficiencies than single-positive cells, even if present in low amounts in cell mixtures or human blood. This preference was confirmed when vector particles were systemically administered into mice. Cell trafficking studies revealed an increased cell entry rate for bispecific over monospecific AAVs. When equipped with an HIV genome-targeting CRISPR/Cas cassette, the vectors prevented HIV replication in T cell cultures. The data provide proof-of-concept for high-precision gene delivery through tandem-binding regions on AAV. Reminiscent of biological products following Boolean logic AND gating, the data suggest a new option for receptor-targeted vectors to improve the specificity and safety of in vivo gene therapy.